2015
DOI: 10.1186/s12991-015-0042-6
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Global Impression-severity score as a reliable measure for routine evaluation of remission in schizophrenia and schizoaffective disorders

Abstract: AimsThis study aimed to compare the performance of Positive and Negative Syndrome Scale (PANSS) symptom severity criteria established by the Remission in Schizophrenia Working Group (RSWG) with criteria based on Clinical Global Impression (CGI) severity score. The 6-month duration criterion was not taken into consideration.MethodsA convenience sample of 112 chronic psychotic outpatients was examined. Symptomatic remission was evaluated according to RSWG severity criterion and to a severity criterion indicated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 36 publications
1
22
1
Order By: Relevance
“…16 In a study investigating the reliability of CGI-S for evaluating remission, a CGI-Schizophrenia Scale severity score ≤ 3 (mildly ill) corresponded to RSWG remission criteria. 17 In the constituent studies, scores at end-point on the CGI-I, the companion component of the CGI-S, supported our post hoc observations of improvement in global disease severity. Across each cariprazine dose that was evaluated, mean CGI-I scores at end-point were between much improved (CGI-I = 2) and minimally improved (CGI-I = 3) and significantly different than placebo in the bipolar disorder studies at week 3 (P < .001 each) [6][7][8] and in the schizophrenia studies at week 6 (P < .01 each).…”
Section: Categorical Cgi-s Improvement and Symptom Severitysupporting
confidence: 69%
See 1 more Smart Citation
“…16 In a study investigating the reliability of CGI-S for evaluating remission, a CGI-Schizophrenia Scale severity score ≤ 3 (mildly ill) corresponded to RSWG remission criteria. 17 In the constituent studies, scores at end-point on the CGI-I, the companion component of the CGI-S, supported our post hoc observations of improvement in global disease severity. Across each cariprazine dose that was evaluated, mean CGI-I scores at end-point were between much improved (CGI-I = 2) and minimally improved (CGI-I = 3) and significantly different than placebo in the bipolar disorder studies at week 3 (P < .001 each) [6][7][8] and in the schizophrenia studies at week 6 (P < .01 each).…”
Section: Categorical Cgi-s Improvement and Symptom Severitysupporting
confidence: 69%
“…In a study investigating the reliability of CGI‐S for evaluating remission, a CGI‐Schizophrenia Scale severity score ≤ 3 (mildly ill) corresponded to RSWG remission criteria 17. In our post hoc category shift analyses, significantly more cariprazine‐ than placebo‐treated patients with schizophrenia shifted to a category with end‐point CGI‐S scores ≤ 3 regardless of the level of baseline disease severity.…”
Section: Discussionmentioning
confidence: 68%
“…The CGI-I is a seven point scale scoring from 1 (very much improved) to 7 (very much worse), with a score of 4 indicating no change. The CGI scales are validated for different psychiatric disorders (Berk et al, 2008;Pinna et al, 2015;Spielmans & McFall, 2006), but not specifically in older adults, although older populations are taken into account in one large study that adequately validated the CGI scales in an inpatient clinic, which showed good overall validity (Berk et al, 2008). We used a scoring guideline and a matrix with examples how to score outcomes in different disorders (Brodaty, Draper, & Low, 2003;Busner & Targum, 2007;Kadouri, Corruble, & Falissard, 2007;Spearing, Post, Leverich, Brandt, & Nolen, 1997).…”
Section: Clinical Global Impressions Of Improvement (Cgi-i)mentioning
confidence: 99%
“…It comprises five items based on a 7-point Likert scale that focus on positive, negative, depressive, cognitive, and overall symptom severity. This scale is considered a simple and reliable measure to evaluate the clinical status and course of the disease during routine clinical practice [32]. The WHODAS 2.0 evaluates six domains of functioning as experienced in the previous 30 days: mobility, self-care, life activities, understanding and communicating, interpersonal interactions, and participation in society [33].…”
Section: Methodsmentioning
confidence: 99%